Imagens holográficas como tema gerador para abordagem dos fenômenos de interferência e difração da luz - Dantas, Samia Abadia (2016)
The development of a teaching learning sequence is reported to approach the light diffraction, interference and polarization phenomena, which can only be understood in view of the wave behavior of light. Taking the holographic images as a subject, the sequence includes the treatment of key concepts such as amplitude, wave length and frequency, required for the desired operativity of the models. The sequence was applied within about 300 students of the second year of morning regular High School in a public school located in Uberlandia, Minas Gerais, Brazil. Based on the theory of conceptual fields by Vergnaud, it was conceived in order to present a wide range of situations, allowing students to experience and dominate them, progressively. The discussion of contents was supported in the projection of slides, allowing activities such as analysis of images, videos and animations and running simulations. Ludic materials handling activities were also carried out and allowed the full participation of students in the dialogues about the characteristics of wave motion, the functional relationship among their physical quantities and representations of interest in this work. For the mathematical treatment for the waves, seeking the interpretation of mathematical expressions, and the construction and interpretation of graphs, we have chosen to apply the Modellus software for its easy handling and free distribution. Questionnaires were answered at different moments, including an initial and a final ones, the last after the regular bimonthly assessments. Our results indicate that the activities performed promoted effective participation and involvement of students, even when the topics with a strong mathematical nature were considered. Although the process of creating holographic images have not been deeply understood by the major part of the students, something which would be expected given the complexity of the issue, the questionnaire answers pointed out an understanding of the characteristics of the wave phenomena of interest. In addition, we found the answers evincing a demystification process technology creation of holograms and the scientist's figure as a “genius”, for which the knowledge would be given in a “divine form”. On the validation of the proposed sequence, it was drafted in the form of a didactic guide for the teacher, which shows an enlargement of the conceptual discussion and details the methodological procedures. This material has been produced aiming to contribute to the approach of these contents, that really appear in the actual curriculum of Physics for the basic education. The following proposal aims to improve the reasoning schemes of the students, from both: the articulation point of view of concepts and the aspect of mathematical representations. We believe that this work can provide a future approach to issues as generation and propagation of sound signals or modern physics topics as wave-particle duality.